Militant Democracy and Its Critics : Populism, Parties, Extremism - Malkopoulou, Anthoula (Edinburgh University Press, 2022)
Should representative governments restrict the democratic rights of their extremist opponents?The first edited collection to boast an international group of political scientists, legal scholars and philosophers debating the urgent question of how to combat anti-democratic extremismAsks whether it is permissable for representative governments to restrict the democratic rights of their extremist opponentsArgues both for and against militant democracy - policies that pre-emptively restrict the rights of antidemocratic movements Militant Democracy refers to the defensive policies democracies use to respond to antidemocratic movements. Can defensive efforts that curtail rights of participation be consistent with democratic values? In this collection of essays, scholars from across politics, philosophy and law address the unresolved practical and theoretical questions concerning democracy and extremism. The collection provides an update to a key contemporary debate in democratic theory and asks us to reconsider the potential promise and costs of militant democracy. ContributorsDamkjær Anne Barsøe, University of Aarhus, DenmarkGiovanni Capoccia, University of Oxford, UK Alexander Kirshner, Duke University, USA Anthoula Malkopoulou, Uppsala University, Sweden Jan-Werner Müller, Princeton University, USALudvig Norman, The Swedish Institute of International Affairs, SwedenBastiaan Rijpkema, Leiden University, NetherlandsRovira Cristòbal Kaltwasser, Diego Portales University, ChileStefan Rummens, KU Leuven, BelgiumAndrás Sajó, Central European University, Hungary Peter Stone, Trinity College Dublin, IrelandSvetlana Tyulkina, University of New South Wales Sydney, AustraliaVincents Tore Olsen, University of Aarhus, Denmark